Optimalisasi ZISWAF sebagai Strategi Pendanaan Berkelanjutan di Perguruan Tinggi Keagamaan Islam (PTKI) - Sari Utami; B Baharuddin (AL HUKMU: Journal of Islamic Law and Economics, 2026)
This study analyzes the urgency of establishing Islamic Religious Higher Education Institutions (PTKI) based on Zakat, Infaq, Alms, and Waqf (ZISWAF) in Indonesia. PTKI play a vital role in shaping the intellectual life of the Muslim community but face financial challenges from traditional funding sources such as government assistance and insufficient tuition fees. Indonesia has enormous potential for ZISWAF, but its utilization in the education sector has not been optimal. This study uses a qualitative approach with document analysis to identify the benefits, cost components, and factors influencing the unit cost per student at ZISWAF-based PTKI. The results indicate that ZISWAF can be a sustainable alternative funding source, improving PTKI's financial independence, educational quality, and educational access for the underprivileged.